1990
DOI: 10.2337/diab.39.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Type II Diabetes in Mexican Americans Predicted by Fasting Insulin and Glucose Levels, Obesity, and Body-Fat Distribution

Abstract: Few data exist on predictors of non-insulin-dependent (type II) diabetes mellitus. We examined body mass index (BMI), ratio of subscapular-to-triceps skin fold (centrality index), and fasting glucose and insulin concentrations as predictors of decompensation to type II diabetes in Mexican Americans, a population at high risk for this disorder. Twenty-eight of 474 initially nondiabetic Mexican Americans developed type II diabetes after 8 yr of follow-up. Converters to diabetes were older and had higher BMIs, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
143
2
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(163 citation statements)
references
References 0 publications
16
143
2
2
Order By: Relevance
“…Like the Pima Indians [3], Mexican Americans are very insulin-resistant and have a high incidence of Type 2 diabetes (T2DM) [4,5]. The goal of the SAM study was to relate the severity of glucose intolerance to the severity of beta-cell dysfunction and insulin resistance in muscle and the liver.…”
mentioning
confidence: 99%
“…Like the Pima Indians [3], Mexican Americans are very insulin-resistant and have a high incidence of Type 2 diabetes (T2DM) [4,5]. The goal of the SAM study was to relate the severity of glucose intolerance to the severity of beta-cell dysfunction and insulin resistance in muscle and the liver.…”
mentioning
confidence: 99%
“…Cross-sectional [3,4,5] and prospective [6,7,8] studies have shown an association between age and body mass index and the prevalence and incidence of Type 2 diabetes. These associations have been consistently reported from different ethnic groups.…”
mentioning
confidence: 99%
“…Both insulin resistance [2] and deficient insulin secretion [3] have been postulated as antecedents of NIDDM. Prospective studies are useful in elucidating the complex relationship between abnormal insulin secretion and peripheral insulin resistance in the pathogenesis of NIDDM.Previous prospective studies have shown that hyperinsulinaemia is a strong predictor of NIDDM [4][5][6][7][8][9][10][11]. Insulin resistance has been inferred on the basis of hyperinsulinaemia in these studies of prediabetic subjects; in non-diabetic subjects, there is a Diabetologia (1997) Summary Although insulin resistance and decreased insulin secretion are characteristic of established non-insulin-dependent diabetes mellitus (NIDDM), which of these metabolic abnormalities is the primary determinant of NIDDM is still controversial.…”
mentioning
confidence: 99%